Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To express the function [tex]\( h(x) = \frac{4}{3 - \sqrt{4 + x^2}} \)[/tex] as the composition of two functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] in such a way that [tex]\( h(x) = (f \circ g)(x) = f(g(x)) \)[/tex], we need to find appropriate functions [tex]\( f \)[/tex] and [tex]\( g \)[/tex].
Let's start by identifying the inner and outer functions corresponding to the given form [tex]\( h(x) \)[/tex].
Given [tex]\( h(x) = \frac{4}{3 - \sqrt{4 + x^2}} \)[/tex]:
1. It's evident that the inner part involves [tex]\( \sqrt{4 + x^2} \)[/tex]. Let’s define [tex]\( g(x) \)[/tex] such that:
[tex]\[ g(x) = \sqrt{4 + x^2} \][/tex]
This simplifies the expression [tex]\( h(x) \)[/tex] to:
[tex]\[ h(x) = \frac{4}{3 - g(x)} \][/tex]
2. Next, we need to determine [tex]\( f(x) \)[/tex] such that [tex]\( f(g(x)) = h(x) \)[/tex]. Here [tex]\( g(x) = \sqrt{4 + x^2} \)[/tex] is already defined. So we get:
[tex]\[ f(g(x)) = \frac{4}{3 - g(x)} \][/tex]
Therefore, our function [tex]\( f(x) \)[/tex] is:
[tex]\[ f(x) = \frac{4}{3 - x} \][/tex]
Putting these functions together, we have the composition of the functions [tex]\( f \)[/tex] and [tex]\( g \)[/tex] such that:
[tex]\[ (f \circ g)(x) = f(g(x)) = \frac{4}{3 - \sqrt{4 + x^2}} \][/tex]
Thus, the correct answer is:
[tex]\[ f(x) = \frac{4}{3 - x} \][/tex]
[tex]\[ g(x) = \sqrt{4 + x^2} \][/tex]
Let's start by identifying the inner and outer functions corresponding to the given form [tex]\( h(x) \)[/tex].
Given [tex]\( h(x) = \frac{4}{3 - \sqrt{4 + x^2}} \)[/tex]:
1. It's evident that the inner part involves [tex]\( \sqrt{4 + x^2} \)[/tex]. Let’s define [tex]\( g(x) \)[/tex] such that:
[tex]\[ g(x) = \sqrt{4 + x^2} \][/tex]
This simplifies the expression [tex]\( h(x) \)[/tex] to:
[tex]\[ h(x) = \frac{4}{3 - g(x)} \][/tex]
2. Next, we need to determine [tex]\( f(x) \)[/tex] such that [tex]\( f(g(x)) = h(x) \)[/tex]. Here [tex]\( g(x) = \sqrt{4 + x^2} \)[/tex] is already defined. So we get:
[tex]\[ f(g(x)) = \frac{4}{3 - g(x)} \][/tex]
Therefore, our function [tex]\( f(x) \)[/tex] is:
[tex]\[ f(x) = \frac{4}{3 - x} \][/tex]
Putting these functions together, we have the composition of the functions [tex]\( f \)[/tex] and [tex]\( g \)[/tex] such that:
[tex]\[ (f \circ g)(x) = f(g(x)) = \frac{4}{3 - \sqrt{4 + x^2}} \][/tex]
Thus, the correct answer is:
[tex]\[ f(x) = \frac{4}{3 - x} \][/tex]
[tex]\[ g(x) = \sqrt{4 + x^2} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.